Authentic recipes from China - Law, Kenneth (Periplus, 2004)
The cuisine of China is widely regarded as one of the finest in the world. This collection of recipes, gathered from the top kitchens of this vast country, presents an exciting range of regional dishes. Included are spicy Sichuan favorites, refined dishes fit for an emperor's table, robust Mongolian fare, and creative Cantonese cuisine. An extensive array of popular foods including appetizers, dips, soups, noodles, and rice dishes enables the reader to participate in China's fascinating history and fast-paced modern era.